La détresse psychologique du personnel médical et paramédical d’anesthésie-réanimation - Halouani, Najla (Pan Afr Med J, 2018)
Anesthesia and intensive care medicine is considered one of the specialties involving more professional stress (PS). On this basis, our study aimed to assess the level of anxiety and PS in the personnel in anesthesia and intensive care and to identify the associated factors. We conducted a cross-sectional, descriptive and analytical study including 54 participants (38 technicians and 16 residents) working in the Departments of Anesthesia and Intensive Care at Habib Bourguiba and Hedi Chaker University Hospitals, Sfax, Tunisia. PS assessment was performed using the Karasek questionnaire. The Hamilton Anxiety Rating Scale (HARS) was used to measure the severity of anxiety symptoms. According to the Karasek questionnaire, the average decision latitude score was 69, the average psychological demand score was 23.9 and the average social support score was 19.6. According to this questionnaire, 40.7% of personnel was stressed and 38.9% was in isostrain condition. Average HARS score was 17.8, average psychic anxiety score was 8.7 and average somatic anxiety score was 9, with a significant difference between the medical and paramedical personnel. Severe to very severe anxiety was recorded in 25.9% of cases. HARS score was correlated to female gender (p=0.017) and to psychiatric histories (p=0.003). This study highlights that medical and paramedical personnel in anesthesia and intensive care is exposed to a significant risk of PS. Changes in working environment as well as learning professional stress management techniques should be proposed.